The Effectiveness of Therapy Combination of Acupressure and Lavender Aromatherapy Toward Elderly Pain with Arthritis Gout: A Quasi-Experimental Study - Vilda, Vilda; Herlinah, Lily; Permatasari, Tria Astika Endah (Indonesian Journal of Global Health Research, 2024)
The total population of the elderly has been rising all over the world. It is predicted with the nature of human aging several health problems will be a new burden including Arthritis Gout. This type of joint disease causes pain in the joints accompanied by stiffness, redness, and edema. A Non-pharmacological approach is strongly needed as combination therapy which has been effective in reducing pain. Acupressure and aromatherapy have been widely used in several populations but limited knowledge in the effect of pain among patients with arthritis gout. Objective. The purpose of this study was to determine the effect of acupressure therapy and lavender aromatherapy on reducing pain in the elderly with gout arthritis. Methods: This research is a quasi-experiment with a two-group pre-test and post-test design approach. Respondents were divided into control and intervention groups. The instrument used in this study is the NRS (Numerical Rating Scale) using Likert Scale 0-10. Data analysis using Independent T-Test. Results: The majority of was in the early phase (45-59 years), female, and had high education. The results of the analysis showed a statistically significant decrease in pain scale h a p-value of 0.001. Conclusion: The combination of acupressure and lavender aromatherapy is effective in lowering pain scales in elderly people with gout arthritis.